Intermittent cold exposure improves glucose homeostasis associated with brown and white adipose tissues in mice - Wang, Tse-Yao (Life Sci, 2015)
AIMS: The discovery of different shades of fat has been implicated in the pathogenesis of obesity-related metabolic disorders. However, the effects of early and intermittent exposure to cold temperature on systemic metabolic changes in adult life remain unclear. MAIN METHODS: To elucidate the impact of cold temperature exposure on metabolic function of adipose tissues, we investigated the glucose homeostasis, activation of brown adipose tissue (BAT) and “browning” of white adipose tissue (WAT) in mice in response to intermittent cold exposure. Mice were exposed to 4 °C, 2 hours per day and 5 days per week, for 14 weeks. Glucose homeostasis was tested via intraperitoneal glucose tolerance test and insulin tolerance test; body fat mass was evaluated using in vivo magnetic resonance imaging; BAT activity was detected primarily by positron emission tomography/computed tomography; and WAT “browning” was evaluated using immunohistochemistry. KEY FINDINGS: Our results showed that 14-week cold exposure improved glucose tolerance and enhanced insulin sensitivity, reduced the relative weights of epididymal and retroperitoneal WAT, increased expressions of UCP1 and PGC1α in subcutaneous adipose tissue. SIGNIFICANCE: Intermittent exposure to cold temperature in early life may improve systemic glucose homeostasis and induce WAT “browning”, suggesting that ambient cold temperature exposure may serve as a promising intervention to metabolic disorders.